Mortality and heavy metals environmental exposure: a study in dogs - Giugliano, Roberta; Crescio, Maria Ines; Cosma, Valeria; Ciccotelli, Valentina; Vivaldi, Barbara; Razzuoli, Elisabetta (Frontiers in Veterinary Science, 2024)
Dogs are human companions and share environmental condition with their owners. Epidemiological studies have shown that dog seems to be a good sentinel animal for the association of diseases and/or mortality provoked by chronic exposure to heavy metals (Cd, Pb). In the present work, we have analysed registered death cases and population collected from the National Canine Registry from 2020 to 2022, involving a dog population of 582564 and 17507 deaths cases. Mortality rate in male and not purebred dogs is higher than female and purebred, respectively. Then, the mortality cases were crossreferenced with the environmental pollution data relating to the concentration of Cd and Pb detected, between the year 2012-2022, in the various municipalities of the Liguria region. We have calculated SMR (Standardized Mortality Rate) all over the region and founded out that mortality increases passing from the eastern to the Ligurian western coast and we observed that the most polluted areas present the highest SMRs (IRR=1.36, 95%CI: from 1.31 to 1.41). Considering dog ages, we have founded that meanwhile young dogs' mortality is not affected by pollution, oldest dogs' mortality (10-20 years old) is strongly affected by it (IRR=8.97, 95%CI from 8.09 to 9.93). Concluding, data suggest the importance of health canine and biomonitors studies and provide a basis to future researches involving both animal and human health.